Teori Perkembangan Piaget dan Vygotsky : Bagaimana Implikasinya dalam Pembelajaran Matematika Sekolah Dasar? - Nina Agustyaningrum; Paskalia Pradanti; Yuliana (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2022)
Mathematics is an important subject whose applications were widely used in life. However, many students have difficulty in learning mathematics, including elementary school students. This study aimed to examine the depth of Jean Piaget's cognitive development and Lev Vygotsky's sociocultural theory and their implication for mathematics learning at elementary school age. This study used a qualitative approach with the literature study method. Sources of data in the form of books, journals, and the results of previous research related to research problems. Data collection in this study was carried out using online searches. Data analysis was done by content analysis. The results of this study indicate that according to Piaget's theory of cognitive development, the thinking stage of students in elementary schools was generally in the concrete operational stage. So that the recommended mathematics learning was in the form of student-centered active learning such as discovery learning and contextual learning methods. Meanwhile, based on Vygotsky's sociocultural theory, he recommends cooperative and collaborative mathematics learning as well as optimizing the existence of scaffolding and social interaction in learning.